Reducing lead time and increasing productivity at a mail order distribution center - Analyses and improvements of reverse logistic processes - Belin, Ellinor; Hedman, Richard (My University, 2010)
The purposes of this master’s thesis are to investigate how lead times of the reverse logistical flow can be reduced and how work methods can be improved at a retailing distribution center. The investigated parts of the distribution center are processes, operations and internal flow related to handling of returned goods. Reverse logistical environments, associated to online and catalog retailing, are characterized by high uncertainties since large diversity of products arrives in small quantities. The project has been conducted by the use of a methods engineering approach. Several studies were made to collect and compile data in order to present a current state of the investigated area. Results from analyzing the current state showed exceptional long lead times, unstable processes and improvement potential in manual operations. From the results, together with the project’s frame of reference, a number of proposed improvements were presented. The improvements aim to reduce lead times in handling of returned goods by reducing buffer sizes, balancing flow of goods and re-planning the manning of workstations. Further, actions which will increase efficiency and simplify routines have also been presented. All suggested improvements contribute to an overall reduction of lead time, a stable flow and increased productivity in returns handling. Keywords: Lead time, productivity, returns handling, distribution center
Keywords: Produktion; Produktionsteknik; Production; Manufacturing engineering